The AAA-type ATPase AtSKD1 contributes to vacuolar maintenance of Arabidopsis thaliana - Shahriari, Mojgan; Keshavaiah, Channa; Scheuring, David; Sabovljevic, Aneta; Pimpl, Peter; Häusler, Rainer E.; Hülskamp, Martin; Schellmann, Swen (The plant journal, 2010)
The vacuole is the most prominent organelle of plant cells. Despite its importance for many physiological and developmental aspects of plant life, little is known about its biogenesis and maintenance. Here we show that Arabidopsis plants expressing a dominant-negative version of the AAA (ATPase associated with various cellular activities) ATPase AtSKD1 (SUPPRESSOR OF K+ TRANSPORT GROWTH DEFECT1) under the control of the trichome-specific GLABRA2 (GL2) promoter exhibit normal vacuolar development in early stages of trichome development. Shortly after its formation, however, the large central vacuole is fragmented and finally disappears completely. Secretion assays with amylase fused to the vacuolar sorting signal of Sporamin show that dominant-negative AtSKD1 inhibits vacuolar trafficking of the reporter that is instead secreted. In addition, trichomes expressing dominant-negative AtSKD1 frequently contain multiple nuclei. Our results suggest that AtSKD1 contributes to vacuolar protein trafficking and thereby to the maintenance of the large central vacuole of plant cells, and might play a role in cell-cycle regulation.